PERLAWANAN BANGSA INDONESIA SEBAGAI FONDASI TERBENTUKNYA KESADARAN NASIONAL DAN KEMERDEKAAN - Ephani Ananda Br Ginting; Nanda Dwi Astri; Elly Prihasti Wuriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Project-Based Learning (PjBL) model on the creative writing skills of eighth-grade students at SMP Cendramata Medan. The research focused on Indonesian language learning, particularly on enhancing students’ creative writing abilities through the application of project-based learning. The method employed was an experimental design with a pretest-posttest format. Data were collected through creative writing tests administered before and after the implementation of the learning model, as well as observations during the learning process.The descriptive analysis revealed that the students’ average pre-test score was 45.00 with a standard deviation of 20.33 and a standard error of 5.871. After the application of the project-based learning model, the average post-test score increased significantly to 78.75 with a standard deviation of 6.784 and a standard error of 1.958 from a total of 12 respondents. This increase of more than 70% indicates that the project-based learning model effectively enhanced students’ creative writing skills. In addition to the improvement in scores, students became more active, engaged in creative thinking, and showed greater interest in producing written work.Based on these findings, it can be concluded that the Project-Based Learning model has a significant impact on students’ creative writing skills. The model not only improves the quality of students’ written products but also encourages independence, creativity, and responsibility throughout the learning process.